The Microbiota and Gut-Brain Axis - ARICIOĞLU, FEYZA (YERKURE TANITIM & YAYINCILIK HIZMETLERI A S, 2016)
The ability of gut microbiota to communicate with the brain and hence modulate behavior is an emerging novel concept in health and disease. The enteric microbiota interacts with the host to form essential relationships that govern homeostasis. Although enteric bacterial fingerprint of each individual is quite unique, there appears to be a certain balance that confers individual's health benefits. A developing number of studies demonstrated that the microbiome of the human digestive tract might have had an effect on the elements of the focal anxious framework (CNS), through recognized pathways called the gut-brain axis. Recent data showed that the human microbiome ecosystem interfered with the brain's development, central signaling systems, and behavior. It has been proposed that the disruption of the human microbiome may contribute to the etiology and course of some psychiatric disorders. Therefore, a decrease in the desirable gastrointestinal bacteria would lead to deterioration in gastrointestinal, neuroendocrine, immune functioning and consequently an illness. This review article presents an overview about the main pathways of the gut-brain axis and consequences of stress to the individual components.
Keywords: brain-gut axis; microbiota; probiotics; anxiety disorders; IRRITABLE-BOWEL-SYNDROME; INTESTINAL MICROBIOTA; BEHAVIOR; DISORDERS; COMMUNICATION; LACTOBACILLUS; SEROTONIN; BARRIER; SYSTEM; RATS